Acute effect of quadriceps stretching on vertical ground reaction force, muscle activity and vertical jump performance - Fantini, C.; Araujo, S.; Pacheco, F.; Menzel, H. J.; Chagas, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to analyze the acute effects of stretching on jumping performance (vertical velocity of the center of mass), vertical ground reaction force (peak force and rate of force development) and electromyography (EMG) of the vastus lateralis (VL) during the countermovement jump (CMJ). Nineteen male individuals performed the CMJ test before and after one quadriceps stretching session. This session consisted of four 20-second repetitions of passive static stretching of quadriceps. The results indicated a significant reduction in the rate of force development, a reduction in the integrated EMG during the eccentric phase and an increase in duration of the concentric phase. However, these alterations did not affect the vertical jump performance.